Distribuição espacial de Sitophilus Zeamais (Coleoptera: curculionidae) em plantios de milho no Sertão Sergipano - Moreira, Jackeline da Silva (2025)
The maize weevil, Sitophilus zeamais Motschulsky, 1855 (Coleoptera: Curculionidae), is one of the main pests affecting maize during the grain maturation and storage phases, leading to losses in biomass and quality. For integrated pest management, it is essential to understand the spatial distribution of this insect while the crop is still in the field. This study aimed to determine the spatial distribution of S. zeamais in maize fields in the semi-arid region of Sergipe, Brazil, using geostatistical analysis. The research was conducted during the 2022 and 2023 harvests in the municipality of Nossa Senhora da Glória, Sergipe. Maize ears were collected from 86 sampling points in the 2022 field and 100 sampling points in the 2023 field. Samples were stored in plastic bags and kept in the laboratory. After 20 days of storage, the ears were monitored and evaluated to quantify the emergence of adult S. zeamais. Spatial distribution was assessed using geostatistical analysis with semivariograms and kriging interpolation, performed in GS+ and QGIS software, respectively. Results indicated spatial dependence described by the exponential model, revealing an aggregated distribution pattern of the insects in the study areas. These findings provide important information for the development of more efficient and targeted pest management strategies.